ELECTROANATOMIC MAPING OF LEFT AND RIGHT VENTRICLES IN A PATIENT WITH VNTRICULAR ECTOPY USING THE CARTO 3 THREE DIMENSIONAL MAPPING SYSTEM - Khan, Qurban Hussain; Asad, Mohammed; Hayat, Azmat; Shabbir, Muhammad; Kamal, Hassan; Khattak, Zahoor Aslam (Pakistan Armed Forces Medical Journal, 2019)
We report a case of suspected right ventricle outflow tract (RVOT) ventricular ectopy and cavotricuspid isthmus (CTI) dependent clockwise atrial flutter presenting two years after surgery for removal of an implantable cardio-verter defibrillator (ICD) lead. The atrial flutter was mapped and successfully ablated using the CARTO-3 three dimensional electroanatomic mapping system. However, mapping of the ventricular ectopy revealed that it did not originate from either the left or right ventricular endocardium and instead likely came from the epicardium, which made ablation too risky to attempt in this patient.